Consumer behavior after the Brazilian power rationing in 2001 - Carreno, E. M. [UNESP]; Sanches, T. L. [UNESP]; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
In June 2001, after a dry period, the level of the water reservoirs in Brazil was below their operational levels. This situation, combined with other historical factors, led the country into a period of power rationing. As expected, power consumption lowered during this period. After December 2001, when the power rationing ended, electrical utilities expected to return to their normal power consumption in a matter of months, but the level of power consumption only returned to its level around years 2004 2005. Consumer behavior went through a change during this period, and the consumers kept this behavior after, leading to electrical and economical consequences until today. This paper presents an analysis of several factors that led to these events, including historical consumption data and comparisons with similar situations. The objective of this analysis is to give helpful information to electrical utilities, that could deal with similar situations, in their load forecasting studies. © 2006 IEEE.
Keywords: Brazilian electrical system; historical consumption data; load management; long term load forecasting; power rationing; series disruption; Electrical systems; Long-term load forecasting; Electric load management; Reservoirs (water); Electric load forecasting